2015
DOI: 10.1039/c5cp03460d
|View full text |Cite
|
Sign up to set email alerts
|

Grain-size dependence of mechanical properties in polycrystalline boron-nitride: a computational study

Abstract: The field of research in polycrystalline hexagonal boron nitride (PBN) has been enjoying extraordinary growth recently, in no small part due to the rise of graphene and the technical advancement of mass production in polycrystalline 2D materials. However, as the grain size in 2D materials can strongly affect their materials properties and the performance of their relevant devices, it is highly desirable to investigate this effect in PBN and leverage the service capability of PBN-based devices. Here we employ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…This means that, for an accurate prediction of strength, it might be necessary to map out all the topological defects in the material, which is not always possible or desirable. The findings for graphene are expected to be applicable also for other 2D materials, as demonstrated by a recent study on fracture in polycrystalline boron-nitride (BN) sheet [133]. Net charge can exist in some defects (such as five-seven rings) in BN sheet [134], whose effect on the material fracture has not yet been fully explored in the literature.…”
Section: Strength and Toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that, for an accurate prediction of strength, it might be necessary to map out all the topological defects in the material, which is not always possible or desirable. The findings for graphene are expected to be applicable also for other 2D materials, as demonstrated by a recent study on fracture in polycrystalline boron-nitride (BN) sheet [133]. Net charge can exist in some defects (such as five-seven rings) in BN sheet [134], whose effect on the material fracture has not yet been fully explored in the literature.…”
Section: Strength and Toughnessmentioning
confidence: 99%
“…Most large-scale 2D materials contain various topological defects [120][121][122] that make the prediction of their failure strength extremely challenging [13,14,31,101,102,104,105,[123][124][125][126][127][128][129][130][131][132][133]. For example, the strength of a bi-crystal graphene is highly dependent on the grain boundary [101,102,123], which was recently explained with a disclination dipole theory [102].…”
Section: Strength and Toughnessmentioning
confidence: 99%
“…Although computational approaches are well suited for this analysis, it has been demonstrated that these catalytic systems cannot be realistically modeled without taking into account support effects . In this spirit, it is appropriate to focus on emerging catalyst supports such as boron nitride based materials, which besides possessing high thermal, mechanical, and chemical resistance, have also been recently investigated as hydrogen storage platforms and in nanocatalysis …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, unlike graphene, h-BN has a binary configuration and its lack of inversion symmetry results in more complex bonding structures with unfavorable homonuclear bonds (Gibb et al, 2013;Li et al, 2015;Liu et al, 2012). The presence of such defects is known to alter the properties of h-BN films (Becton & Wang, 2015;Li et al, 2015;Mortazavi et al, 2015). Hence, to fully exploit these scalable films and achieve better growth procedures, deep insights into their structural configuration, defects, and growth behaviors are critical.…”
Section: Introductionmentioning
confidence: 99%